Faiz’s Three Selected Poems: An Analysis of Sequential Ideology - Asif, Muhammad; Ashraf, Muhammad (sourcecoder, 2024)
Faiz’s poetic collections "Dast-e-Saba" and "Zindan Nama" are reminiscent of his days of captivity (1951-1955) during the Rawalpindi Conspiracy Case. Primarily, his writings reflect those sorts of mental engagements and sensations which have their origin in progressive Urdu poetry. Hence, "Nisar main teri galiyon ke...", "Zindan ki ek shaam" and "Zindan ki ek subah" carry the essence of this background. These three poems are included in his poetic collection "Dast-e-Saba". These poems are enriched with those amorous symbols and devices of classical ghazals which are the persistent feature of Faiz’s poetry in general. Faiz has articulated the themes related motherland, patriotism and love and beloved with great perseverance. He envisions the homeland as a beloved. Thus, these three selected poems not only reflect Faiz’s eloquence but also his observations and struggles in social activism.